Enhanced Artificial Neural Network Applications for Spatial Localization Stochastic EM Radiation Sources - Zoran Stankovic, Nebojsa Doncov, Ivan Milovanovic, Bratislav Milovanovic (Journal of Information & Systems Management, 2022)
To ensure the enhanced artificial neural network applications for spatial localization stochastic EM radiation sources, we present a system with results. We have given the stochastic sources near field representation with antenna arrays and dipole elements. Besides, the correlation matric calculation architecture is presented. It will help to develop neural models for the 1D and 2D DoA estimation. In addition, we have presented the environment when sources are moving towards one direction and their corresponding position is decided by one protrusion angle with linear antenna. We have supported the illustrations with neural model capability to the issues of the DoA calculation for the sources.